Design Of “Our Market” Sales Information System In The Web-Based Dringu Traditional Market - Yulianto, Yahya; Dyah Ariyanti; Rahma, Ary Analisa (Universitas Panca Marga, 2023)
As technology advances and people's needs for shopping, considering that currently shopping can be accessed through applications. The Probolinggo District Office of Industry and Trade facilitates buying and selling without entering the market, shopping online through the WhattsApp and Instagram applications with the